Bioaccumulation of Copper and Stress Response In Chili Plants Under Organic Management: Bioaccumulation of Copper and Stress Response In Chili Plants Under Organic Management - Sapto Priyadi; Haryuni; Teguh Supriyadi; Daryanti (JURNAL ILMIAH AGRINECA, 2026)
Copper (Cu) is an essential micronutrient for plant growth, but at elevated concentrations it can become toxic, particularly in agricultural systems transitioning to organic practices where organic fertilizers are applied intensively. This study aimed to evaluate the bioaccumulation of Cu and physiological stress responses in chili plants (Capsicum annuum L.) cultivated under varying doses of cattle manure in a transitional organic farming system. The experiment was arranged in a completely randomized block design with manure application rates ranging from 15 to 50 tons per hectare. Observed parameters included yield, Cu concentration in the fruit, and food safety indicators such as Bioaccumulation Factor (BAF), Estimated Weekly Intake (EWI), Provisional Tolerable Weekly Intake (PTWI), and Target Hazard Quotient (THQ). The results showed that increasing manure dosage significantly enhanced fruit yield and Cu accumulation. However, no traces of cadmium (Cd) or lead (Pb) were detected, and Cu levels remained within acceptable food safety limits. The highest Cu concentration was observed at the highest manure dose, yet BAF and PTWI values indicated minimal risk to human health. These findings suggest that while cattle manure can improve crop productivity, it may also contribute to Cu accumulation that could trigger oxidative stress in plants. This research contributes to the scientific understanding of micronutrient dynamics, food safety, and plant stress physiology within sustainable organic farming systems.